DETERMINATION OF PHYSIO-CHEMICAL PROPERTIES OF OLEANDER SEED OIL FOR BIODIESEL PRODUCTION (Nigerian Journal of Technology, 2013)
The need for alternative feedstock for biodiesel production due to the competition in vegetable oil production for human consumption and biodiesel production necessitated a study in the physiochemical properties of Nerium Oleander seed, a non-edible ornamental plant. The objectives were to determine the physical, chemical properties of the Nerium Oleander seed suitable for biodiesel production. The mean major, minor and intermediate diameters of twenty Nerium Oleander seeds were 3.53 cm, 1.85 cm and 1.98 cm respectively. The volume, density and sphericity of the seeds were reported to as 7.70 cm3, 0.49 g/cm3 and 0.69 respectively. The seed oil exhibited good chemical properties for biodiesel production with a viscosity of 46.58mpa/s at 30oC, Free Fatty Acid (FFA) of 3.92%, cloud point of 2oC and a flash point above 200oC. The ash content, moisture content, melting point, density at 15oC, Cetane number and the heat of combustion were reported as 1.44%, 0.33%, 8oC, 0.898 g/cm3, 63.55 and 125.37 KJ/L, respectively. The cetane index of Nerium Oleander seed oil had high cetane index when compared to the ASTM standard for diesel fuels. It was concluded that the Oleander seed is an alternative feedstock for biodiesel production